Case report: Neglected subacute thyroiditis: a case following COVID-19 vaccination - Shuai Yang; Shuai Yang; Ting Guan; HuanYi Yang; YiRong Hu; Yan Zhao (Frontiers in Medicine, 2024)
We report a case of overlooked Subacute Thyroiditis (SAT) potentially induced by the administration of a COVID-19 vaccine. This case prompted a thorough review of the existing literature to elucidate possible mechanisms by which immune responses to the COVID-19 vaccine might precipitate thyroid damage. The primary objective is to enhance the clinical understanding and awareness of SAT among healthcare professionals. Subacute thyroiditis is a prevalent form of self-limiting thyroid disorder characterized by fever, neck pain or tenderness, and palpitations subsequent to viral infection. The development of numerous SARS-CoV-2 vaccines during the COVID-19 pandemic was intended to mitigate the spread of the virus. Nevertheless, there have been documented instances of adverse reactions arising from SARS-CoV-2 vaccines, such as the infrequent occurrence of subacute thyroiditis. While the majority of medical practitioners can discern classic subacute thyroiditis, not all cases exhibit typical characteristics, and not all systematic treatments yield positive responses. In this study, we present a rare case of subacute thyroiditis linked to the administration of the SARS-CoV-2 vaccine. A previously healthy middle-aged female developed fever and sore throat 72 h post-inoculation with the inactivated SARS-CoV-2 vaccine. Initially attributing these symptoms to a common cold, she self-administered ibuprofen, which normalized her body temperature but failed to alleviate persistent sore throat. Suspecting a laryngopharyngeal disorder, she sought treatment from an otolaryngologist. However, the pain persisted, accompanied by intermittent fever over several days. After an endocrinology consultation, despite the absence of typical neck pain, her examination revealed abnormal thyroid function, normal thyroid antibodies, heterogeneous echogenicity on thyroid ultrasonography, and elevated levels of Erythrocyte Sedimentation Rate (ESR) and C-Reactive Protein (CRP). These findings led to a consideration of the diagnosis of SAT. Initially, she was treated with non-steroidal anti-inflammatory drugs (NSAIDs) for her fever, which proved effective, but her neck pain remained uncontrolled. This suggested a poor response to NSAIDs. Consequently, steroid therapy was initiated, after which her symptoms of fever and neck pain rapidly resolved.